Optimizing the Duties and Functions of Educators in the Islamic Education Environment from the Al-Qur'an Perspective - Nursyamsiyah, Siti; Huda, Hairul (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2024)
Every educator has duties and functions in working in educational institutions. However, these duties and functions have not been fulfilled optimally by educators. Some educators know their responsibilities and some know their duties and functions but do not carry them out well. In fact, in the Al-Qur'an it is stated in Surah Al-Isra: verse 24 that as an educator you should have an attitude of nurturing, nurturing, and educating. However, in reality, there are still many cases where educators only transfer knowledge. Meanwhile, the caring attitude has not been fully implemented optimally. The purpose of this research is to explain the duties and functions of educators carried out in the Islamic education environment. Second, it explains the Al-Quran's perspective on the duties and functions of educators. The method used in this research uses qualitative research with a case study approach. The object of this research was carried out at Islamic educational institutions, especially educators in the Muhamamdiyah environment in Jember Regency. Data collection techniques use observation of educators' performance, interviews with Muhammadiyah school supervisors, civil service bureaus, school principals, and educators, and documentation. The data analysis technique applies source triangulation. The results of this research found that optimizing the duties and functions of educators in the Islamic education environment can run optimally with policy socialization and scheduled or open evaluations. These duties and functions include online attendance, activeness in recitation, performance evaluation, providing performance allowance rewards, nurturing, nurturing, guiding, perfecting, and building characterful student behavior. Apart from that, the duties and functions of educators are to be mentors for junior educators and as an honest, kind, and open work team. From an Islamic perspective, duties and functions are based on Ali Imran's letter: 104; Surah Ar Rahman: 4; Surah Al-Anbiya:80; Luqman's letter: 13; and Surah Al Isra': 24.